A Review on Recent Advancement on Age-Related Hearing Loss: The Applications of Nanotechnology, Drug Pharmacology, and Biotechnology - Chester, Jacqueline (Pharmaceutics, 2021)
Aging is considered a contributing factor to many diseases such as cardiovascular disease, Alzheimer’s disease, and hearing loss. Age-related hearing loss, also termed presbycusis, is one of the most common sensory impairments worldwide, affecting one in five people over 50 years of age, and this prevalence is growing annually. Associations have emerged between presbycusis and detrimental health outcomes, including social isolation and mental health. It remains largely untreatable apart from hearing aids, and with no globally established prevention strategies in the clinical setting. Hence, this review aims to explore the pathophysiology of presbycusis and potential therapies, based on a recent advancement in bile acid-based bio-nanotechnologies. A comprehensive online search was carried out using the following keywords: presbycusis, drugs, hearing loss, bile acids, nanotechnology, and more than 150 publications were considered directly relevant. Evidence of the multifaceted oxidative stress and chronic inflammation involvement in cellular damage and apoptosis that is associated with a loss of hair cells, damaged and inflamed stria vascularis, and neuronal signalling loss and apoptosis continues to emerge. New robust and effective therapies require drug delivery deeper into the various layers of the cochlea. Bile acid-based nanotechnology has gained wide interest in its permeation-enhancing ability and potential for numerous applications in treating presbycusis.